Settlement strategies in Eastern Central Europe during the maximum extent of the last glacial ice sheet. (20th April 2021) - Škrdla, Petr; Vlach, Marek; Nejman, Ladislav; Bartík, Jaroslav; Demidenko, Yuri E.; Rychtaříková, Tereza
Abstract: Compared to the unparalleled cultural achievements and population boom of the Gravettian hunter-gatherers in Eastern Central Europe, the succeeding Last Glacial Maximum (LGM) occupation is signified by extremely low populations densities, which is reflected in the scant archaeological record. This chrono-cultural contrast can be generally attributed to the severe climatic downturn of the LGM. An attempt to find common cultural patterns that could link individual LGM populations has been only partially successful. An evaluation of the environmental factors using GIS and multivariate spatial analysis has tested twelve geomorphological characteristics and has found a strong pattern where sites were chosen for their seclusion in small valleys and natural amphitheatres probably because they offered partial protection from the elements. The overall difficulty in finding common patterns between the scattered LGM populations is partly due to our gaps in knowledge of the cultural lifeways of this period, but it is also due to a likely greater cultural heterogeneity of the scattered, small and highly mobile LGM populations living in the cold, arid environment of Eastern Central Europe at the time.